Effect of foliar application of Fe and Zn on growth, flowering and yield of gerbera (Gerbera jamesonii) under protected condition - PAL, SUNDER; BARAD, A V; SINGH, A K; KHADDA, B S; KUMAR, DALEEP (The Indian Journal of Agricultural Sciences, 2016)
The experiment on effect of foliar application of Fe and Zn on growth, flowering and yield of gerbera (Gerbera jamesonii Bolus) under protected condition was carried out during 2010-2011. The experiment was laid out in Completely Randomized Design (CRD) with three replications comprising six levels of micronutrients, i.e. control (M1), FeSO4 @ 0.2% (M2), FeSO4 @ 0.3% (M3), ZnSO4 @ 0.2% (M4), ZnSO4 @ 0.3% (M5) and FeSO4 + ZnSO4 @ 0.2% each (M6). Growth, flowering, yield and quality attributes influenced by different levels of micronutrients, viz. highest plant height (20.11 and 28.56 cm), plant spread (35.56 and 42.00 cm1) and number of leaves/plant (10.44 and 15.22) at first flower appearance and at full bloom stage, respectively. The number of suckers/plant (3.89) at last harvest, fresh (128.11g) and dry weight (44.11g), flowering span (275.70 days), number of flowers/plant (15.70) and per square meter (157.40) and yield of flowers (15.70 lacs/ha), diameter of flower (11.64 cm), length of flower stalk (54.00 cm) and thickness (6.22 mm), number of florets/ flower (213.33), longevity (16.44 days) and vase life (10.28 days) of flower were significantly highest when micronutrient was sprayed at level of FeSOZnSO4 + ZnSOZnSO4 @ 0.2% each (MZnSO6). Whereas, minimum days to the appearance of first flower bud (48.11) and days to opening the first flower (54.67) were also recorded in MZnSO6 (FeSOZnSO4 + ZnSOZnSO4 @ 0.2% each) level of micronutrient. It is concluded that for the application of FeSOZnSO4 + ZnSO4 @ 0.2% each (M6) at monthly intervals up to 12 months. From economic point of view, it was observed that this treatment was also most profitable as it recorded the highest net returns.